Pressure Prediction Using Material Balance Equation/ Case History/ Ghani Field/Libya (Sebha University Conference Proceedings, 2025)
This study examines the material balance equation (MBE) for predicting future reservoir pressure in the Ghani field / farrud reservoir. The reservoir's complexity made material balance calculations challenging. Relevant properties were extracted, and composite PVT set and relative permeability curves were obtained from PVT and SCAL data. Cumulative production and injection data from 1980-2024 were screened and optimized. The material balance calculations were executed for the historical production/injection period up to the end of 2024, employing various aquifer models. To match average pressure behavior, an aquifer influx was superimposed on the model. The MBAL software revealed energy contributions, indicating aquifer influence, leading to the successful application of the Carter-Tracy aquifer model and demonstrating good consistency with observed data. Ultimately, the Carter-Tracy model was used for water influx calculations. The energy plot indicated that water injection and influx were the primary contributors to production over time, while fluid expansion and PV compressibility played a minor role. A notable discrepancy in the history match post-2002 was attributed to the diminishing effects of the water influx model and the increasing influence of the water injection system, which accounted for approximately 94% of total reservoir energy.